PEMBERDAYAAN INDUSTRI KECIL NIRA AREN MENJADI KOMODITAS EKONOMI DI DESA TUBUHUE KECAMATAN KOTA KEFAMENANU - Yesus Armiro Korbaffo; Felisisima Afoan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The purpose of this service is to empower and assist in the development of the indigo palm sugar industry into brown sugar / stone sugar in order to produce more varied products so that they can be sold more widely. And grow and provide knowledge to the brown sugar industry, able to make processed palm sugar products by setting the right selling price, choosing a fixed location. The location of the service is the Tubuhue Village, Kefamenanu City District, North Central Timor Regency. with 5 members of the sugar palm sugar craftsman group. The methods used in this service are: the first Preparation, is a service program planning which includes: Location Survey, Coordination with service location partners, Determination of training time, Determination of target and target trainees and Planning of training materials and the second namely Implementation with the intention to increase public knowledge about improving skills in processing palm sap, in this implementation it is grouped into two stages namely Lecture, and Demonstration. What is expected from this service is Encouraging rural communities to better utilize palm juice by processing palm sugar into a variety of products and fostering an attitude of independence and quality of life in rural communities so that family income and welfare increase.